(untitled) (Journal of Partial Differential Equations, 2004)
The uniqueness and existence of BV solutions to Dirichlet problem of doubly degenerate parabolic equations of the following form ∂u∂t = div(A(|∇B(u)|)∇B(u)) in Q_T = Ω × (0, T) are studied.